EFFECTIVE LEARNING OF MATHEMATICS: FROM THEORY TOPRACTICE - Tsafe, A. K. (Sokoto Educational Review, 2012)
It was generally believed that in the art of teaching regardless of discipline or level of operation of the learner, knowledge can best be imparted subject to some prerequisite features to be acquired by both encoders (teachers) and decoders (learners) in what psychologist called delivery and reception theory. For instance, the teacher has to undergo a prescribed training to be acquainted with the knowledge; likewise, the learner has to be ready and capable of receiving the information that may be given to him by the teacher. This may possibly seme as the basis through which students can best learn and understand Mathematics. In this regard, this paper explores what could be termed as an approach suitable for making students of Mathematics best learn Mathematics and offers a conceptual framework of the reasons why student faces challenges associated with Mathematics learning. The paper also contains the contributions of some notable psychologists on how best Mathematics could be taught to students at various stages of development. This ranges from Piagetians stages, Brunner and Gagne.